Curcumin-loaded nanostructured lipid carrier induced apoptosis in human HepG2 cells through activation of the DR5/caspase-mediated extrinsic apoptosis pathway - Wang Fengling; Ye Xi; Zhai Dandan; Dai Wenting; Wu Yifan; Chen Jin; Chen Weidong (Acta Pharmaceutica)
Curcumin is a lipophilic anti-cancer compound extracted from turmeric. Our previous study demonstrated that the curcumin-loaded nanostructured lipid carrier (Cur-NLC) exhibits superior anti-cancer activity in inhibiting proliferation as well as inducing apoptosis of human HepG2 cells compared to native curcumin. This study aims to unveil the mechanisms underlying the pro-apoptotic effect of Cur-NLC on HepG2 cells. Evidence indicates that low expression of death receptors (DRs) on cancer cell membranes leads to attenuated apoptosis signaling. This study showed that Cur-NLC significantly increased total expression of DR5 protein while simultaneously upregulated cell membrane expression of DR5. Cur-NLC significantly increased caspase-8 and caspase-3 activities, accompanied by increased apoptosis. Furthermore, enhanced apoptosis was inhibited in the presence of a pan-caspase inhibitor, Z-VAD-FMK. Therefore, Cur-NLC induced activation of the extrinsic apoptosis pathway via modulating the DR5/caspase-8/-3 mediated apoptosis pathway in HepG2 cells, suggesting that Cur-NLC is a promising therapeutic agent or supplement for the treatment of hepatocellular carcinoma.